(5x-3)/3=4

Simple and best practice solution for (5x-3)/3=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-3)/3=4 equation:


x in (-oo:+oo)

(5*x-3)/3 = 4 // - 4

(5*x-3)/3-4 = 0

(5*x-3)/3+(-4*3)/3 = 0

5*x-4*3-3 = 0

5*x-15 = 0

(5*x-15)/3 = 0

(5*x-15)/3 = 0 // * 3

5*x-15 = 0

5*x-15 = 0 // + 15

5*x = 15 // : 5

x = 15/5

x = 3

x = 3

See similar equations:

| 4logx^3-3logx^2=12 | | (-7)=g+(-5) | | 5a+1=8 | | 5a+56=-56 | | U-24=(-27) | | 5x+2y+30=0 | | 28=w-(-5) | | (12.50-1.95)x=125 | | 3/2x-4 | | C=qn+r | | -33=-17-n | | 7x-78=-65 | | (-14)=t+(-25) | | 14-6v=-4(2v-1) | | (-14)=j-(-24) | | -11-w=-36 | | 4(2x-3)-3(x-2)+2=4-(x-7) | | y+2x=27 | | S-11=(-34) | | (z^2-2iz)*(z^2+25)=0 | | 3x+3=-25 | | -11=s+5 | | (-11)=13+x | | 15/25=y/30 | | (-15)+g=(-5) | | (2c+9)(c+5)= | | f(x)=6x^3+8x^2+3 | | 6(1-2x)-x=-46 | | B-17=-38 | | 6+2x=5-(7x) | | J+13=37 | | a^2+4ab+4b^2=0 |

Equations solver categories